(untitled) (Architecture Image Studies, 2026)
In this paper, the thematic focus and development of research in music education in Malaysia has been examined by a bibliometric analysis of the articles using VOSviewer. Peer-reviewed journals with the keywords music, education, and Malaysia were gathered in the sources of credible databases to visualize the patterns of co-occurrence and thematic relations of research topics. The analysis shows that the most central keywords are education, music and Malaysia, which are directly related to such themes as teacher development, parental involvement and philosophies of music education. The results prove that the cultural context, educator identity and collaborative practices in teaching affect the research on music education quality and in Malaysia. This research provides an overview of the academic discussion of quality music education in Malaysia by combining quantitative mapping with qualitative interpretation. Not only the existing research strengths are addressed in the results, but also existing gaps and opportunities for further investigation are also outlined. Finally, the research has implications in practice for teachers, researchers, and policy makers who may take music education further by being data-driven, sustainable and culturally responsive.